Changes in cerebral glucose metabolism after 3 weeks of noninvasive electrical stimulation of mild cognitive impairment patients. Issue 1 (December 2016) - Yun, Kyongsik; Song, In-Uk; Chung, Yong-An
Abstract Background Mild cognitive impairment (MCI) is a syndrome that disrupts an individual's cognitive function but preserves activities of daily living. MCI is thought to be a prodromal stage of dementia, which disrupts patients' daily lives and causes severe cognitive dysfunction. Although extensive clinical trials have attempted to slow or stop the MCI to dementia conversion, the results have been largely unsuccessful. The purpose of this study was to determine whether noninvasive electrical stimulation of MCI changes glucose metabolism. Methods Sixteen MCI patients participated in this study. We used transcranial direct current stimulation (tDCS) (2 mA/day, three times per week for 3 weeks) and assessed positron emission tomography (18 F-FDG) before and after 3 weeks of stimulation. Results We showed that regular and relatively long-term use of tDCS significantly increased regional cerebral metabolism in MCI patients. Furthermore, subjective memory satisfaction and improvement of the memory strategies of participants were observed only in the real tDCS group after 3 weeks of stimulation. Conclusion Our findings suggest that neurophysiological intervention of MCI could improve glucose metabolism and transient memory function in MCI patients.